Integration of Social Identities in Interreligious-Group Relations - Pertiwi, Ika Hana; Faturochman, Faturochman (Faculty of Psychology, Universitas Gadjah Mada, 2023)
In the context of interreligious group relations, grassroots society tends to demonstrate adaptation strategies to promote harmonious social living. Based on the social identity perspective, such conditions encompass the dynamic process in which diverse religious group identities are endorsed within a coherent superordinate identity. This study explores the dynamics of integration as a strategy to maintain religious harmony. A qualitative case study was conducted in a rural community with diverse religious groups in Central Java. Data were gathered through participative observations, semi-structured interviews, casual conversations, and document analysis. We employed an abductive strategy to analyze the rich empirical materials gathered. The findings reveal the integrative construction of a common ingroup identity, that embraces the essence of unity in diversity. As a strong common ingroup identity indicates, it requires the development of a transcendent identity at the subgroup level. This process encourages a positive orientation towards others to preserve equality among groups. Of utmost importance, this integration most likely plays a pivotal role in addressing both social harmony and social tension. This study highlights that the strategy of integration is explained through the formation of an inclusive common ingroup identity, that illustrates the node of bonding and bridging for existing religious groups to live together.